COVID-19: Ultraviolet-C device for protecting operation theatre personnel: a pilot controlled study - John, Pravin Hector; Thanakumar, John A. C.; Rao, Arcot Mohan; Kapali, Neelamekam Thoppa; Seshadri, Mandalam S. (International Journal Of Community Medicine And Public Health, 2020)
Background: Covid-19 is currently wide-spread in urban and rural India. Health care workers (HCW) contract disease when exposed to inoculum in enclosed spaces namely operation theatre (OR) or Intensive care unit (ICU). 1.8-5 % of health care workers (HCW) tested positive in Delhi and Dutch experience is similar. 8% of HCW who contract COVID-19 die. Commercial filters have been advocated by various surgical societies and despite routine use of these filters, HCWs continue to get infected. Ultraviolet C (UVC) irradiation has been in use for bacterial and viral decontamination of surfaces, liquid and gaseous media. Methods: In this study, we describe a closed UVC chamber with built-in HEPA filters to decontaminate and sterilize effluent gases from patients undergoing laparoscopic or open surgical procedures to make it free of SARS-COV-2 virus and minimize risk of infection for the OR crew. We also report an adaptation of this device for anesthesia. We compare SARS-CoV-2 infections in HCW in our hospital, where this device is routinely used, with outcomes from another hospital with identical personal protection measures, performing similar surgical procedures but without the device. Results: COVID-19 incidence is significantly reduced with the use of this device compared to a similar hospital with similar surgical protocols but without the device Conclusions: In the current pandemic situation where a number of HCWs get infected or succumb to SARS CoV2 infection, measures such as UVC chamber described in this paper provide additional protection to HCWs in the OR. They are of considerable public health importance and serve to boost the sagging morale of HCWs.